Quantum photonics based on metasurfaces - Jun Liu (Institue of Optics and Electronics, Chinese Academy of Sciences, 2021)
From metamaterials to metasurfaces, optical nano-structure has been widely investigated for novel and high efficiency functionalities. Apart from the intrisinsic properties of composite material, rich capabilities can be derived from the judicious design of metasurfaces, which enable more excellent and highly integrated optical devices than traditional bulk optical elements. In the meantime, the abundant manipulation abilites of light in the classical domain can be carried over into quantum domain. In this review, we highlight recent development of quantum optics based on metasurfaces, ranging from quantum plasmonics, generation, manipulation and appplication of quantum light to quantum vaccum engineering etc. Finally, some promising avenues for quantum optics with the help of optical metasurface are presented.